The quest for the Messiah the history, literature and theology of the Johannine community - Painter, John (Edinburgh, Scotland T. and T. Clark, 1999)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. John -- criticism, interpretation, etc; Bible. N.T. John, 1st -- Criticism, interpretation, etc; Jesus Christ -- history of doctrines -- early church, ca. 30-600.; Messiah -- Biblical teaching